Robust Memristive Fiber for Woven Textile Memristor. (10th April 2022) - Liu, Yue; Zhou, Xufeng; Yan, Hui; Zhu, Zhengfeng; Shi, Xiang; Peng, Yahui; Chen, Lin; Chen, Peining; Peng, Huisheng
Abstract: Memristors with an intrinsic crossbar structure and high computing capability offer promising opportunities for the flexible information‐processing component that can well integrate with the interwoven structure of electronic textiles. However, it remains difficult to achieve uniform inorganic memristive layer at nanometer thickness on the curved surface of fiber electrode, thus hindering the applications of textile memristors. Here, a high‐performing and reliable textile memristor made of robust Pt/CsPbBr3 fiber through an electric‐field‐assisted assembly method is reported. The textile memristor exhibits a cycle to cycle variation of less than 8% and an average set voltage of ≈ 0.16 V, which is lower than that of the majority of planar metal‐oxide memristors. The flexible and mechanically robust Pt/CsPbBr3 fibers are woven into a scalable textile memristor array with good device‐to‐device reproducibility. This textile memristor can be seamlessly integrated with textile electronics toward a smart clothes system to accurately process complicated physiological information, providing an effective interactive interface for intelligent healthcare. Abstract : An efficient and facile electric‐field‐assisted assembly method is employed to achieve a uniform and robust inorganic memrisitive layer on a curved fiber electrode for the high‐performing textile memristor. The resultant textile memristor array woven by the Pt/CsPbBr3 fiber exhibits a low set voltage of ≈0.16 V, high cycle‐to‐cycle uniformity, and good device‐to‐device reproducibility.